PERANCANGAN ALAT BANTU UNTUK ARRANGING OUTER DEVICES CRASH STOP DI PT XYZ - zulkarnain, muhammad; Sirait, Ganda (LPPM Universitas Putera Batam, 2020)
ABSTRACT The process is fast and does not cost much, is an action that needs to be done by the company to be able to achieve profits. Design is a strategy to support the achievement of the company in the production that is carried out, namely carrying out design activities which aim to provide a new design of the process by designing tools as a solution to the problem of its long production time. PT XYZ is a manufacturing company in the electronics industry which is engaged in the production of hard disk drive components, but the company did not arrive at the assembly, only making spare part components of these products. Problems occur when arranging the outer device crash stop charger product into the packaging media tray which is done one by one using tweezers, so that it has an impact on the long preparation time. Arranging the product into the media tray. Products that have round dimensions and diameters (2.63 x 1.08 x 4.03) mm, make it difficult for operators to arrange into holes in the tray and require a long time of 9.13 minutes. Design for.Manufacturing.and Assembly is the deepening of two methods namely Design for.Manufactur design that focuses on ease in manufacturing and DFA (Design for Assembly) design focuses on ease when the product assembly process. The successful implementation of JIG Arranging tools using the DFMA design method gave an increase in the Arranging process by 130%, where before 38 processes were 88 times a day. The Arranging process experienced an acceleration of time in a process where previously using Tweezers took 9.13 minutes, now using JIG Arranging only needed 3.95 minutes. Keywords: Design, Design For Manufacturing and Assembly, Productivity